2012
DOI: 10.1029/2011jb008862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduced near‐field entrainment of overpressured volcanic jets on plume development

Abstract: [1] Volcanic plumes are often studied using one-dimensional analytical models, which use an empirical entrainment ratio to close the equations. Although this ratio is typically treated as constant, its value near the vent is significantly reduced due to flow development and overpressured conditions. To improve the accuracy of these models, a series of experiments was performed using particle image velocimetry, a high-accuracy, full-field velocity measurement technique. Experiments considered a high-speed jet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…This hypothesis is based on the self‐similarity of pure jets or plumes (e.g., Batchelor, ). On the other hand, because eruption columns are not self‐similar, the value of k varies considerably with height (e.g., Carazzo et al, ; Kaminski et al, ; Saffaraval et al, ; Suzuki & Koyaguchi, ). Here we calculate the values of Q in , truev̄, and truer̄ from the 3‐D simulations without gravity using equations and (see Appendix B) and determine k as a function of height (cf.…”
Section: Results Of 3‐d Simulations Without Gravitymentioning
confidence: 99%
“…This hypothesis is based on the self‐similarity of pure jets or plumes (e.g., Batchelor, ). On the other hand, because eruption columns are not self‐similar, the value of k varies considerably with height (e.g., Carazzo et al, ; Kaminski et al, ; Saffaraval et al, ; Suzuki & Koyaguchi, ). Here we calculate the values of Q in , truev̄, and truer̄ from the 3‐D simulations without gravity using equations and (see Appendix B) and determine k as a function of height (cf.…”
Section: Results Of 3‐d Simulations Without Gravitymentioning
confidence: 99%
“…As we simulated smaller‐scale eruptions ( trueṁ0= 2.51×10 6 kg s −1 ) than these previous studies, we infer that there is some specific mechanism that suppresses entrainment around volcanic plumes/jets as the magma discharge rate decreases. In addition to these mechanisms, it has also been suggested that the entrainment can be suppressed in supersonic flows [ Saffaraval et al , ; Suzuki and Koyaguchi , ]. To better constrain the values of k for volcanic plumes/jets over a wide range of eruption conditions, more comprehensive parameter studies using 3‐D numerical simulations including supersonic flow would be necessary.…”
Section: Estimation Of Entrainment Efficiencymentioning
confidence: 99%
“…This assumption is appropriate for slender plumes (Morton et al, 1956;Woods, 1988;Linden, 2000), where the length scale of radial variations is much smaller than the length scale for vertical variations. The assumption may not be appropriate very near to the vent, where the erupted material can have a substantial over-pressure (Woods and Bower, 1995;Ogden et al, 2008b;Saffaraval et al, 2012). This alters the flow dynamics (Woods and Bower, 1995;Ogden et al, 2008b,a), in particular the turbulent mixing processes, such that a different parameterization of entrainment is required (Saffaraval et al, 2012).…”
Section: The Plumerise Model Of Moist Wind-blown Volcanic Plumesmentioning
confidence: 99%
“…The assumption may not be appropriate very near to the vent, where the erupted material can have a substantial over-pressure (Woods and Bower, 1995;Ogden et al, 2008b;Saffaraval et al, 2012). This alters the flow dynamics (Woods and Bower, 1995;Ogden et al, 2008b,a), in particular the turbulent mixing processes, such that a different parameterization of entrainment is required (Saffaraval et al, 2012). However, the pressure in the near vent jet rapidly adjusts to atmospheric pressure (Saffaraval et al, 2012) and therefore we expect the model results to be little affected by the simplified description (Saffaraval et al, 2012).…”
Section: The Plumerise Model Of Moist Wind-blown Volcanic Plumesmentioning
confidence: 99%